Mobility for learners and staff – higher education students and staff mobility inter-institutional agreement 2014-20[21] between programme countries – Università degli Studi di Sassari [University of Sassari] and Universidade Lusíada de Lisboa - Universidade Lusíada de Lisboa (2015)
- Cooperate for exchange of students and/or staff in the context of the Erasmus + programme. - Erasmus subject area – Architecture and town planning; - Law